How Sensor, Signal, and Imaging Informatics May Impact Patient Centered Care and Care Coordination - Voros, S.; Moreau-Gaudry, A.; Section Editors for the IMIA Yearbook Section on Sensor, Signal and Imaging Informatics (Yearbook of Medical Informatics, 2015)
Objective: This synopsis presents a selection for the IMIA (International Medical Informatics Association) Yearbook 2015 of excellent research in the broad field of Sensor, Signal, and Imaging Informatics published in the year 2014, with a focus on patient centered care coordination.Methods: The two section editors performed a systematic initial selection and a double blind peer review process to select a list of candidate best papers in the domain published in 2014, from the PubMed and Web of Science databases. A set of MeSH keywords provided by experts was used. This selection was peer-reviewed by external reviewers.Results: The review process highlighted articles illustrating two current trends related to care coordination and patient centered care: the enhanced capacity to predict the evolution of a disease based on patient-specific information can impact care coordination; similarly, better perception of the patient and his treatment could lead to enhanced personalized care with a potential impact on care coordination.Conclusions: This review shows the multiplicity of angles from which the question of patient-centered care can be addressed, with consequences on care coordination that will need to be confirmed and demonstrated in the future.
Keywords: Medicine personalization; care coordination; innovative technologies; biomedical imaging; patient centered modelling